A Mixed-Methods Evaluation of a Wellbeing Programme Designed for Undergraduate Students: Exploring Participants’ Experiences Using Interpretative Phenomenological Analysis - Maria-Christina Vourda; Jess Collins; Radhika Kandaswamy; Mário Cesar do Nascimento Bevilaqua; Carolina Kralj; Zephyr Percy; Naomi Strauss; Patricia A. Zunszain; Gisele P. Dias (Education Sciences)
The mental health struggles of university students have been the focus of a substantial amount of research worldwide. To tackle this, universities have developed initiatives to promote student wellbeing. Here, we highlight Time to Thrive (TTT), a co-designed online programme based on positive and coaching psychology and neuroscience literacy to support undergraduate students to thrive at university. This study examines the effectiveness of TTT on undergraduate student wellbeing and explores students’ subjective experiences as participants in TTT. A mixed-methods randomised controlled trial was conducted with an intervention group (n = 18) and a later access control group (n = 26) to verify the impact of TTT on psychological wellbeing, mental wellbeing, and resilience. Participants completed the Short Warwick-Edinburgh Mental Wellbeing Scale (SWEMWBS), the Flourishing Scale (FS), and the Brief Resilience Scale (BRS) pre-post intervention. Following programme completion, intervention group participants were interviewed about their experience with TTT (n = 5), and their reflections were analysed using Interpretative Phenomenological Analysis (IPA). Participation in TTT significantly improved psychological wellbeing in the intervention group, controlling for pre-TTT scores. Three themes were developed through IPA: the differing functions of TTT, the personal impact of TTT, and placing students who need it the most at the heart of TTT. These findings suggest that university-delivered initiatives can effectively foster undergraduates‘ wellbeing. Embedding TTT and relevant programmes within the curriculum may facilitate engagement and impact. Moreover, evidence sustaining their effectiveness may inform policy for broader application in higher education.